PdO impact on the activity of hydrocarbon oxidation with oxide catalysts - Ponomarenko, A.; Ved, V. E.; Satayev, M.; Saipov, A. (My University, 2016)
The palladium component influence on the catalytic activity of a catalyst was investigated based on transition-metal oxides deposited on α-Al2O3 carrier in the process of hydrocarbon catalytic thermal destruction. It has been determined that the value of surface concentrations of PdO deposited on Co3O4 doesn’t effect on the achievable conversion degree when using the obtained catalytic converter. It is suggested that PdO facilitates the interfacial diffusion of atomic oxygen on the catalyst oxide component due to support it in an oxidized state. Adsorbed on palladium oxygen migrates on cobalt oxide in the composition of this catalyst. At the expense of this process oxygen passivation of Pd-Co3O4/γ-Al2O3 catalyst is overcome and its high reaction activity is ensured. Our research is evidence that Co3O4 performs the role of active centers on a corundum carrier in the reaction of catalytic thermal hydrocarbon oxidation. Additionally injected PdO into the catalyst composition promotes to the cobalt phase enrichment by oxygen.
Keywords: gas emissions; catalytic conversion; catalyst unit; hydrocarbon conversion; transition-metal oxides; palladium oxide